Regeneration rates of Dendrobium bobby messina plbs with ascorbic acid using PVS2 vitrification - Jessica Jeyanthi James Antony; Chan Lai Keng; Sreeramanan Subramaniam (Syiah Kuala University, 2012)
Cryopreservation techniques using PVS2 vitrification was applied on PLBs of Dendrobium Bobby Messina, with survival monitored through observations of growth rate and the 2,3,5-triphenyltetrazolium chloride (TTC) analyses. The parameters optimized were PLBs size, preculture concentration, preculture duration, PVS2 incubation temperature and duration. The optimized parameters obtained were 3-4mm of PLBs precultured in 0.2M sucrose for 1 day, treated with a mixture of 2M glycerol and 0.4M sucrose supplemented with half strength liquid MS media at 25°C for 20 minutes and subsequently dehydrated with plant vitrification solution 2 (PVS2) at 0°C for 20 minutes prior storage in liquid nitrogen. Following rapid warming in a water bath at 40°C for 90 seconds, PLBs were washed with a half strength liquid MS media supplemented with 1.2M sucrose. Subsequently, PLBs were cultured on half strength semi-solid MS media supplemented with 2% (w/v) sucrose in the absence of growth regulator. The optimized vitrification method was successful in preserving this orchid as it produced growth recovery in cryopreserved PLBs up to 40%. Ascorbic acid was added in the media to evaluate the regeneration process of cryopreserved PLBs. However, growth recovery rate was only 10% at 0.6mM ascorbic acid. RAPD analysis using 6 primers indicated that cryopreserved and non-cryopreserved PLBs from vitrification method were genetically faithful to the mother plant. However, 3 primers showed polymorphism and 1 primers indicated partial polymorphism between the cryopreserved and non-cryopreserved PLBs in comparative to the mother plant.